Legal And Human Right Protection For Victim of Malpractice - Ali Azhar; KMS. Novyar Satriawan Fikri; Muanif Ridwan (Faculty of Law, Universitas Pekalongan, 2024)
One of the main concerns in regard to medical law and healthcare is malpractice. In Indonesia, medical law, additionally referred to as health law, is still a relatively new field of study. The numerous focus on health law, particularly on physicians and hospitals, contrasts with the recently established medical law and the recently acknowledged notion of malpractice. Thus, the issues at hand include how patients' and their families' rights to receive medical information, how to settle disagreements between them and the defendants, and how much the legal procedure settles for in situations of negligence. This study seeks to address the issues surrounding medical disputes and the reasons for patients' and their families' struggles in exercising their right to receive medical data. That it is challenging to prove malpractice lawsuits because it is challenging to access the medical records of patients impacted by malpractice cases